USE OF BAZALT FABRIC FOR LIGHT FILTERS IN CEMENT MANUFACTURING - Umirzakov Zukhriddin Akhtamjonovich (Journals Park Publishing, 2024)
Cement production take out industry surroundings atmosphere man-made a pollutant from the fields one is counted. This attitude with this in process into the air coming out dust catch to stay important to the point have In the article Ferghana cement enterprises in the region using vacuum cleaners structures and light methods of formation of basalt fabric in filters and this study according to done experimental affairs result given . Fabric preparation method and order learned them those that are used in practice with related technical and economic reasoning done.
Keywords: Cement industry, dust handles, light filters, weaving technology, fiberglass fabric, basalt fabrics, ecology.